2007
DOI: 10.1021/jp063841m
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic and Thermodynamic Study of the Glycosidic Bond Cleavage in Deoxyuridine

Abstract: Density functional theory was used to study the thermodynamics and kinetics for the glycosidic bond cleavage in deoxyuridine. Two reaction pathways were characterized for the unimolecular decomposition in vacuo. However, these processes are associated with large reaction barriers and highly endothermic reaction energies, which is in agreement with experiments that suggest a (water) nucleophile is required for the nonenzymatic glycosidic bond cleavage. Two (S(N)1 and S(N)2) reaction pathways were characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
131
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(141 citation statements)
references
References 84 publications
(243 reference statements)
9
131
0
Order By: Relevance
“…13,16,27 Other studies that examine both the S N 1 and S N 2 mechanisms report prohibitively large activation energies for the S N 1 dissociation step, and thus conclude that the synchronous mechanism is favored. 25,26,29 In addition, most studies do not contain the empirically proposed oxacarbenium cation intermediate. [24][25][26]29 For example, two studies have reported a reaction intermediate where the nucleobase reattaches to the sugar through a different connectivity compared with the corresponding natural nucleoside, 26,29 such as O2 of thymine glycol bound to C1′ of the sugar moiety.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,16,27 Other studies that examine both the S N 1 and S N 2 mechanisms report prohibitively large activation energies for the S N 1 dissociation step, and thus conclude that the synchronous mechanism is favored. 25,26,29 In addition, most studies do not contain the empirically proposed oxacarbenium cation intermediate. [24][25][26]29 For example, two studies have reported a reaction intermediate where the nucleobase reattaches to the sugar through a different connectivity compared with the corresponding natural nucleoside, 26,29 such as O2 of thymine glycol bound to C1′ of the sugar moiety.…”
Section: Introductionmentioning
confidence: 99%
“…25,26,29 In addition, most studies do not contain the empirically proposed oxacarbenium cation intermediate. [24][25][26]29 For example, two studies have reported a reaction intermediate where the nucleobase reattaches to the sugar through a different connectivity compared with the corresponding natural nucleoside, 26,29 such as O2 of thymine glycol bound to C1′ of the sugar moiety. 29 A reaction intermediate whereby the nucleobase (directly or indirectly) abstracts a proton from C2′ of the sugar has also been reported for both nucleoside hydrolysis 25,26,29 and enzymatic depurination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 This is in contrast to regular Born-Oppenheimer-like molecular dynamics, where the initial guess of the SCF optimization is based on some extrapolation of the self-consistent solutions from previous time steps, 2,[28][29][30][31][32] for example,…”
Section: Geometric Integrationmentioning
confidence: 99%
“…Born-Oppenheimer molecular dynamics is computationally expensive compared to Car-Parinello dynamics because of the requirement to reach a self-consistent field (SCF) solution in each timestep. However, the number of SCF cycles and thus the computational cost can be strongly reduced by using an initial guess for the electronic degrees of freedom ρ(t n+1 ) (here represented by the electron density), which is given by an extrapolation from previous time steps [5,8,9,17,18,19]. The electronic extrapolation scheme, combined with the SCF procedure, can be seen as an adiabatic propagation of the electronic degrees of freedom, * Corresponding author: Email amn@lanl.gov where…”
mentioning
confidence: 99%